The native Iranian soil bacteria with high potential to produce extracellular methionine gamma-lyase - Nasirian, Matin; Mobini-Dehkordi, Mohsen; Khosravian, Pegah (Frontiers in Microbiology, 2024)
This study aimed to screen native methionine gamma-lyase (L-methioninase) producing bacteria from soil samples and optimize the culture media for enhanced enzyme production using statistical design. Three bacteria, Pseudomonas mosselii, Ralstonia solanacearum, and Cytobacillus kochii, were identified as novel L-methioninase producers, which alternative source of L-methioninase for cancer treatment could be utilized alongside other therapeutic agents. The bacteria were isolated from various garden soils and cultured on a modified M9 medium and screened by Nessler reagent. According to Bergey’s manual of systematic bacteriology, identification tests determined the morphological, physiological, and biochemical characterizations. Further identification was performed using the analysis of the 16 s rDNA gene sequences using PCR and universal bacterial primers. The optimization of medium constituents for L-methioninase production was performed in two steps using Response Surface Methodology (RSM). The first step used the “one factor at a time” method to screen and identify critical medium components for L-methioninase production. The second step used the Box–Behnken design to assess quadratic effects and two-way interactions between variables and determine the response’s nonlinear nature. The study found that three isolates produced L-methioninase, namely Pseudomonas mosselii spp.MN02 (GenBank PP431975), Ralstonia solanacearum spp.MN02 (GenBank PP431636), and Cytobacillus kochii spp.MN02 (GenBank PP432622). Among these, Pseudomonas mosselii spp.MN02 produced the highest amount of L-methioninase and was therefore chosen for enzyme production optimization process. The maximum L-methioninase production of 1.5 ± 0.1 U/mL was obtained at a pH 6, and the best nitrogen source was yeast extract (1% concentration). The influence of different carbon sources revealed that glucose was the best carbon source for L-methioninase production (3.25 ± 0.1 U/mL). The optimization experiments using the Box–Behnken design predicted that L-methioninase would have an activity of 12.56 U/mL under optimal conditions, including 2% glucose, 2% yeast extract, pH 6, and temperature at 30°C. In conclusion, this study presents a promising new methods for identifying potential L-methioninase producers and optimizing the culture medium for more enzyme production by microbial fermentation. This could pave the way for developing a drug that assists in human cancers treatment.